Land use imperils plant and animal community stability through changes in asynchrony rather than diversity - Nico Blüthgen (Nature Portfolio, 2016)
Long-term stability of ecological communities is vital for maintaining ecosystem functioning. Here, Blüthgen et al. show that greater land-use intensity in grasslands and forests can have negative impacts on the stability of plant and animal communities, driven primarily by variation in asynchrony between species.